Pengembangan Video Termediasikan Augmented Reality sebagai Electronic Performance Support System dalam Pembelajaran - Yerry Soepriyanto; Basith Rahmatullah (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2016)
Students sometimes find it difficult to illustrate learning content in the form of conceptual knowledge. Therefore, this development aims to produce video products mediated by Augmented Reality which are valid for use in learning performance support electronic systems (Electronic Performance Support Systems). A marker is placed on the teaching material module in the image part that illustrates a concept, so that when students do not fully understand it, the smartphone camera used as a marker detector captures and runs the video. This study uses Sadiman's development method to develop Augmented Reality mediated videos. The result of the development is Augmented Reality mediated video which is used as a learning performance support system in a valid category.